Optical coherence tomographic insights of very late stent thrombosis of a second-generation drug-eluting stent: a case report. Issue 12 (30th November 2021) - Otaal, Parminder Singh; Gawalkar, Atit A; Shunmugarajan, Ajay
Abstract: Background: Very-very late stent thrombosis (VVLST) occurring more than 5 years after implantation of drug-eluting stent (DES) is extremely rare, being restricted to few case reports. Mainly described with first-generation stents, this life-threatening complication has not been described with later-generation stents. We describe the first case of VVLST occurring 3309 days (>9 years) after implantation of second-generation DES. Case summary: A 62-year-old man presented with the acute coronary syndrome. He has a history of percutaneous coronary intervention (PCI) to the right coronary artery using the three second-generation DES more than 9 years ago. Coronary angiogram revealed in-stent restenosis (ISR) with doubtful angiographic thrombus. Optical coherence tomography (OCT) confirmed the diagnosis of stent thrombosis (STh) localized to the stent overlap zone with underlying ISR. Patient underwent OCT-guided PCI with DES implantation and was discharged on dual antiplatelet therapy including ticagrelor. He is doing well on follow-up at 6 months. Discussion: Stent thrombosis can occur in second-generation stents nearly a decade after implant. Stent overlap segment is more prone to neo-atheroma formation and vulnerable plaque leading to STh. In addition to confirming the diagnosis, OCT provides exciting insights into the underlying mechanism. This has implications for long-term antiplatelet therapy in patients implanted with multiple stents.